Multifunctional oral delivery systems for enhanced bioavailability of therapeutic peptides/proteins - Ying Han; Zhonggao Gao; Liqing Chen; Lin Kang; Wei Huang; Mingji Jin; Qiming Wang; You Han Bae (Elsevier, 2019)
In last few years, therapeutic peptides/proteins are rapidly growing in drug market considering their higher efficiency and lower toxicity than chemical drugs. However, the administration of therapeutic peptides/proteins is mainly limited in parenteral approach. Oral therapy which was hampered by harsh gastrointestinal environment and poorly penetrating epithelial barriers often results in low bioavailability (less than 1%-2%). Therefore, delivery systems that are rationally designed to overcome these challenges in gastrointestinal tract and ameliorate the oral bioavailability of therapeutic peptides/proteins are seriously promising. In this review, we summarized various multifunctional delivery systems, including lipid-based particles, polysaccharide-based particles, inorganic particles, and synthetic multifunctional particles that achieved effective oral delivery of therapeutic peptides/proteins. KEY WORDS: Multifunctional delivery systems, Oral, Bioavailability, Macromolecules, Peptides and proteins, Gastrointestinal environment, Epithelial barriers, Nanoparticles